Effect of deoxynivalenol and T-2 toxin in malt amylase activity - Buffon, Jaqueline Garda (2010)
The objective of this work was to evaluate the effect of DON and T-2 toxin levels on the malt amylase activity. The malt was contaminated in accordance with central composite design experiment with DON and T-2 toxin levels until 1000 ng/g. The activities of the enzymes were evaluated by Bernfeld method. The increase in T-2 toxin concentration inhibited the a-amylase activity. However, the increase of both toxins concentration caused inverse effect. The interaction between toxins indicated synergetic effect on the b-amylase activity. An increased activity occurred when the toxins contamination levels in malt were higher (1000ng/g malt). The trichothecenes interfered with the performance of aminolitic enzymes in the stage of malting, resulting in a significant model for enzymatic activity of b-amylase.